2016
DOI: 10.1007/s10584-016-1837-4
|View full text |Cite
|
Sign up to set email alerts
|

Experience of extreme weather affects climate change mitigation and adaptation responses

Abstract: The winter of 2013/2014 saw a series of severe storms hit the UK, leading to widespread flooding, a major emergency response and extensive media exposure. Previous research indicates that experiencing extreme weather events has the potential to heighten engagement with climate change, however the process by which this occurs remains largely unknown, and establishing a clear causal relationship from experience to perceptions is methodologically challenging. The UK winter flooding offered a natural experiment to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
226
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 351 publications
(279 citation statements)
references
References 46 publications
(61 reference statements)
12
226
0
8
Order By: Relevance
“…Consequently, adaptive behavior is not always viewed as politically feasible by public administrations (Patterson et al, 2018;Thaler et al, 2018). Nevertheless, stronger engagement with individuals in flood risk management also demands a new role of public administration (shifted from engineering knowledge toward a stronger focus on project management and communication knowledge), also in terms of conducting further actions in climate change mitigation strategies (Demski, Capstick, Pidgeon, Sposato, & Spence, 2017;Scolobig, Prior, Schröter, Jörin, & Patt, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, adaptive behavior is not always viewed as politically feasible by public administrations (Patterson et al, 2018;Thaler et al, 2018). Nevertheless, stronger engagement with individuals in flood risk management also demands a new role of public administration (shifted from engineering knowledge toward a stronger focus on project management and communication knowledge), also in terms of conducting further actions in climate change mitigation strategies (Demski, Capstick, Pidgeon, Sposato, & Spence, 2017;Scolobig, Prior, Schröter, Jörin, & Patt, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…People residing in flooding-prone areas were more likely to form the belief of climate change than those having heat-wave discomfort experience only. The relationship was further justified by Demski et al [20], who found additional significance of direct experience of extreme weather events and claimed that citizens who were affected by severe storms in the winters of 2013/2014 showed a higher level of vulnerability assessment and climate change awareness than the other individuals. The above-mentioned studies largely imply a pattern between the risk perception and hazard mitigation, and such a pattern can be explained by the PMT.…”
Section: The Linkages Between Risk Experience Perception and Mitigamentioning
confidence: 93%
“…extreme weather events such as cyclones and floods) to anthropogenic climate change (see, e.g. Demski, Capstick, Pidgeon, Sposato, & Spence, 2017). Were this possible, it would provide politicians with more focusing events to attract public attention to the meta problem of climate change (see, e.g.…”
Section: Severitymentioning
confidence: 99%